Empirical Study On Digital Storytelling As A Communication Strategy Among Algerian Social Network Users - Meslem, Hanane; Abbaci, Ayoub (جامعة الوادي - University of Eloued, 2023)
Facing a major growth in social networks use in Algeria, companies are increasingly resorting to digital strategies. Digital storytelling, consisting of relating facts in narrative forms, is one of the communication strategies adopted nowadays, aiming at capturing online consumers. To measure the success of this strategy in terms of appreciation and usefulness, we conducted a quantitative study with a sample of 204 Algerian social network users. The findings led us to the conclusion that digital storytelling could be a valuable approach to build an online communication strategy.
مقال
Keywords: internet users ; digital storytelling ; social networks